THE PECULIARITIES OF THE RECONSTRUCTION OF UKRAINIAN TERRITORIAL COMMUNITIES IN THE CONTEXT OF THE EUROPEAN GREEN DEAL - Sakun, Oleksandra; Shkola, Viktoriia (Socio-economic relations in the digital society, 2023)
The article focuses on delineating the nuances of post-war community recovery within the context of the European Green Deal. The research aims to identify the features and challenges of community recovery in the post-war period, considering the principles outlined in the European Green Deal. An analysis of the losses incurred by territorial communities in Ukraine due to the conflict with russia is conducted, along with quantifying the percentage of territories that were occupied and require restoration. Key difficulties on the path to implementing green community recovery in the current stage are identified, and the principles of green recovery for Ukrainian communities are elucidated and characterized. The article underscores that the recovery of Ukrainian communities should be a systemic process, ensuring a long-term outcome in the form of modernization changes and sustainable development for Ukraine. It asserts that post-war recovery should not merely involve the reconstruction of what was destroyed but should be oriented towards contemporary ecological standards and the vector of European integration. This includes the extensive use of modern energy resources, innovative energy-saving technologies, decarbonization, and more. The article contends that the Green Course has the potential to play a pivotal role not only in the immediate restoration of damaged ecosystems but also in addressing long-term threats related to climate change. The article supports the idea that Ukraine’s adherence to the European Green Deal and its continued implementation can be an effective instrument on the path to Ukraine’s green recovery. Overall, it provides insights into the comprehensive approach required for post-war recovery, emphasizing alignment with contemporary ecological standards and the European integration trajectory. The article concludes that Ukraine’s alignment with the European Green Deal can be a potent tool in steering the country towards a sustainable and green recovery.